A tyranny for the good of its victims the ugly truth about stakeholder capitalism - Puzder, Andrew F. (Tantor Media, Inc., 2025)
Asset manager mega-giants BlackRock, State Street, and Vanguard have accumulated unprecedented levels of stock ownership in every major US company. Voting the shares they hold for clients allows these companies to force their own ""environmental, social, and governance"" or ""ESG"" agenda on the American corporate sector and, by extension, on all of us. An asset manager's traditional duty is to maximize returns for its investors, but these financial elites expand their duties through ""stakeholder capitalism,"" the idea that a company is responsible not only for its actual shareholders, but for everyone who is affected by the company. Thus, they can impose their preferred ESG goals under the guise of benefiting an amorphous group of non-investors. This elite-dominated economic system is nothing more than socialism in sheep's clothing. ""ESG"" defines the champagne socialist agenda that would devastate the working and middle classes globally. Now, in the face of rising opposition, these financial elites are rebranding--shifting their terminology to conceal their intent. A Tyranny for the Good of its Victims exposes how these elites have pursued--and will continue to pursue--their ESG goals: to transform our consumer-driven free-market economy into one that is subject to their elitist demands, overriding the will of the people whom they deem incapable of self-government.
Online resource; title from title details screen (O'Reilly, viewed April 15, 2025)
Keywords: Capitalism -- Social aspects; Social responsibility of business; Free trade; Entreprises; Responsabilité sociale; Libre-échange; Audiobooks; Livres audio